Dementia Care Research and Psychosocial Factors - Garcia-Serrano, A (2025)
BACKGROUND: Verbal fluency tasks reveal the influence of cultural-linguistic backgrounds on word retrieval. A recent cross-linguistic study on animal fluency in Korean- and English-speaking individuals with stroke aphasia found that Korean-speakers generated more zodiac animals rooted in East Asian-culture than English-speakers. Their findings highlight the importance of considering cultural factors in word retrieval and the need for further research in other neurological communication disorders. We examine whether cultural differences in animal fluency emerge between Korean- and English-speaking individuals with Alzheimer s disease (AD) by analyzing clustering and switching patterns across both traditional Western-based and zodiac animal categories, assessing their potential as predictors of cognitive function. METHOD: Thirty-six participants (18 Korean-AD, 18 English-AD) were matched for age, sex, and Mini-Mental State Examination (all p > .05), except for education (p